Penerapan Prepopulated Data Pajak Masukan Pada Aplikasi E-Faktur 3.0 Dan Kesesuaiannya Dengan Peraturan PPN - Bayu Firdaus, Adi; Marfiana, Andri (Educoretax, 2021)
The purpose of this study is to analyze more deeply about the application of prepopulated data, especially for input Value Added Tax (VAT) on e-Faktur 3.0. The application of prepopulated data is analyzed in terms of rules and technical implementation. Such as the impact of its applicaction for taxpayers and tax authorities, conformity with VAT regulations, mechanisms of use, problems in use, and the impact in improving compliance with the delivery of VAT period tax returns seen through the timeliness of reporting. The result of the study indicate that the application of prepopulated data has an impact for taxpayers and the tax authorities to be more facilitated in carrying out VAT administration. Related to alignment with current VAT regulations, there is no need to change the rules because the nature of prepopulated data is only technical in helping reporting. The mechanism using prepopulated data consists of several steps that are easy to apply. Prepopulated data does not directly have an impact in improving the timeliness of reporting VAT period tax returns and the impact is only seen 6 months after application. Finally, the main problem of data is the process of synchronizing and updating data that is not / late to enter the prepopulated database. Tujuan dari penelitian ini adalah untuk menganalisis lebih dalam mengenai penerapan prepopulated data khususnya untuk pajak masukan pada e-Faktur 3.0. Penerapan prepopulated data dianalisis dari segi aturan dan teknis pelaksanaannya. Seperti dampak penerapannya bagi Wajib Pajak dan fiskus , kesesuaian dengan peraturan PPN, mekanisme penggunaan, masalah dalam penggunaan, dan dampak dalam meningkatkan kepatuhan penyampaian SPT Masa PPN yang dilihat melalui ketepatan waktu pelaporan. Hasil penelitian menunjukkan bahwa penerapan prepopulated data memberikan dampak bagi Wajib Pajak dan fiskus untuk lebih dimudahkan dalam menjalankan administrasi PPN. Terkait keselarasan dengan aturan PPN saat ini belum perlu dilakukan perubahan aturan karena sifat prepopulated data hanya bersifat teknis dalam membantu pelaporan. Mekanisme penggunaan prepopulated data terdiri dari beberapa langkah yang mudah untuk diaplikasikan. Prepopulated data tidak secara langsung memberi dampak dalam meningkatkan ketepatan waktu pelaporan SPT Masa PPN dan dampaknya baru terlihat 6 bulan pasca penerapan. Terakhir, permasalahan utama prepopulated data adalah proses sinkronisasi dan update data yang tidak / terlambat masuk pada database prepopulat.